Cod ranching in the Westfjords : a political, social, and spatial analysis - Gaines, Graham, 1982- (2013)
This research aims to identify the legal, political, and social contexts necessary for the successful implementation of cod ranching projects in the Westfjords of Iceland. With the technical components tested and economic viability shown, cod ranching has been slow to develop mainly due to social and political obstacles. One such obstacle concerns the allocation of a large area of a fjord to an exclusive user, which could potentially displace fishing effort. Interviews with government agency personnel, municipal representatives, and fishermen are conducted and analyzed to determine the necesssary measures to be taken for cod ranching to become recognized as a legal, socially responsible method of harvesting wild cod. Spatial and statistical analyses based on historical catch data is conducted to determine potential ranching sites which can restrict commercial fishing without causing significant fishing displacement. The results of this study will serve as a cornerstone in the overall feasibility analysis of cod ranching and will provide researchers, entrepreneurs, and community leaders with valuable information on whether to, how to, and where to attempt a cod ranching project. Vaxtarsamningur Vestfjarða